Results of the implementation of the virtual educational platform Central University of Ecuador - Cadena Vela, Susana Graciela (2017)
The Ecuadorian university has mainly trained professionals, most courses and careers are performed with usual practices and there is little innovation in the use of new tools that favor learning, in the last five years there were about eighty careers and each one with an average of sixty subjects. The common is focused on the knowledge transmission pending the achievement of learning through more active and participative didactics. In the searching to innovate teaching in order to improve learning, it is proposed the insertion of new information and communication technologies in the university work, that is done in the implementation of a Virtual Platform, with the main purpose to support in the teaching-learning process with a visible product which is the management of an academic portfolio for teachers and students. The proposed implementation of the Platform is carried out with a permeable effect according to the levels of the teaching interests, it is considered as a complement to the teaching activities and certainly it does not pretend to replace the presence of the teacher in the classroom, even more so that the teaching is rooted with a strong exclusivity in the teaching staff. The first step to make implementation effective is to determine what virtual educational platform is used, which is done considering the type of software (Open Source), usage, popularity, support, programming code, adaptability and capitalization. Applications have been implemented including in the concept of e-portfolio. The activities (file, creation of courses or modules, tasks, labels, questionnaire, forum, glossary, URL among others) that the platform counts on are varied and allow to be a true learning complement for the teaching. Finally, it is important to describe the results in both the pilot and final stages and characterize through the participating teachers and students as part of the universe and the number of courses that are implemented.